2018
DOI: 10.1080/10903127.2018.1502383
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Incivility Among Nationally Certified EMS Professionals and Associations with Workforce-Reducing Factors and Organizational Culture

Abstract: Nearly half of respondents experienced incivility once a week or more, and incivility was associated with potential workforce-reducing factors. Further research is needed to understand how organizational climate and interpersonal behaviors in the workplace affect the EMS workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…While surveys of EMS personnel from local agencies or single states often achieve higher response rates (5,56), the response rates for electronic surveys of nationally-certified EMS personnel typically range from 10 to 12% (2,8,57), so the 19% response rate achieved in the current study was better than expected. Nevertheless, to help overcome this limitation, weighting was used to increase the representativeness of respondents to the overall target population of nationally-certified EMS personnel.…”
Section: Limitationsmentioning
confidence: 68%
See 2 more Smart Citations
“…While surveys of EMS personnel from local agencies or single states often achieve higher response rates (5,56), the response rates for electronic surveys of nationally-certified EMS personnel typically range from 10 to 12% (2,8,57), so the 19% response rate achieved in the current study was better than expected. Nevertheless, to help overcome this limitation, weighting was used to increase the representativeness of respondents to the overall target population of nationally-certified EMS personnel.…”
Section: Limitationsmentioning
confidence: 68%
“…Typical response rates to electronic surveys among nationally-certified EMS professionals have been between 10-12% (2,7,8). To adjust for nonresponse and differential response rates, survey weights were created based on variables that are related to response rates in this population, specifically certification level, sex, and minority status (28).…”
Section: Missing Data and Survey Weightingmentioning
confidence: 99%
See 1 more Smart Citation
“…EMS providers are in the frontline of care provision to patients, where patients' family members may not be in good and stable mental conditions. Therefore, they are at great risk for threat and violence [13]. Another potential source of physical injury to EMS providers is related to ambulance crashes [38][39][40].…”
Section: Critical Conditions Of Ems Provisionmentioning
confidence: 99%
“…Consequently, they experience high levels of stress and suffer from chronic stress. Studies showed that 22% of EMS providers deal with stress-related complications [3,4] such as anxiety, irritability, social isolation, sleep disorder [5][6][7][8], job dissatisfaction, burnout [9][10][11], workplace incivility, leaving the profession, suicide [12][13][14] post-traumatic stress disorder, risk behaviors, psychological problems, and depression, and are more likely to commit medical errors [15][16][17].…”
Section: Introductionmentioning
confidence: 99%